A novel technique of laparoscopic reduction of incarcerated internal supravesical hernia via peritoneal incision: A case report. (2020) - Matsui, Yugo; Murakami, Teppei; Horita, Kenta; Ishida, Satoshi; Matsuda, Shotaro; Tayama, Aoi; Sakata, Ryutaro
Highlights: There is no golden standard for surgical procedure for internal supravesical hernia. There are previous reports of surgery by open laparotomy, laparoscopy and anterior approach. Various methods for bowel reduction have been described for other hernias, but none by peritoneal incision. The incarcerated small bowel was safely reduced by peritoneal incision in our case. Abstract: Introduction: Laparoscopic reduction techniques for internal supravesical hernia have not been discussed much in literature. Case presentation: A 90-year old woman was admitted for symptoms of intestinal obstruction. She was diagnosed with small bowel strangulation by CT scan and laparoscopy was performed. Laparoscopy revealed a mass medial to the medial inguinal fold with tightly incarcerated small bowel. The bowel could not be reduced by traction or external compression, and required incision of the hernia ring. The tight incarceration posed a risk of bowel injury and so we performed peritoneal incision in a similar manner to the TAPP approach for loosening and precise incision of the hernia ring. The bowel was successfully reduced and the hernia was repaired by partial sac resection. Discussion: Surgical methods as well as reduction technique were reviewed from previous literature. Procedures with open laparotomy, laparoscopy and anterior approach have been described, but details of reduction were not seen in many of these reports. Various methods have been described for bowel reduction in other hernias, but none involving peritoneal incision. This is the first report describing bowel reduction via the peritoneal incision technique. Conclusion: Internal supravesical hernia may pose difficulty in bowel reduction, but the peritoneal incision technique allows safe incision of the hernia ring under laparoscopic situations.